2019
DOI: 10.1186/s12879-018-3638-z
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of disputed rpoB mutations among Mycobacterium tuberculosis isolates phenotypically susceptible to rifampicin in a country with a low incidence of multidrug-resistant tuberculosis

Abstract: BackgroundAccurate drug susceptibility testing (DST) of Mycobacterium tuberculosis in clinical specimens and culture isolates to first-line drugs is crucial for diagnosis and management of multidrug-resistant tuberculosis (MDR-TB). Resistance of M. tuberculosis to rifampicin is mainly due to mutations in hot-spot region of rpoB gene (HSR-rpoB). The prevalence of disputed (generally missed by rapid phenotypic DST methods) rpoB mutations, which mainly include L511P, D516Y, H526N, H526L, H526S, and L533P in HSR-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 40 publications
1
34
0
Order By: Relevance
“…Another important finding was that most (77.4%) of the isolates with disputed mutations were of the Beijing lineage, although a possible association between disputed mutations and a specific genotype has not been observed in other studies (22,43). Of note, four of the five isolates with disputed mutations reported by Ho et al (22) were of the Beijing lineage, and interestingly, three of the four Beijing lineage isolates were isolated from patients who were born in China.…”
Section: Discussionmentioning
confidence: 80%
“…Another important finding was that most (77.4%) of the isolates with disputed mutations were of the Beijing lineage, although a possible association between disputed mutations and a specific genotype has not been observed in other studies (22,43). Of note, four of the five isolates with disputed mutations reported by Ho et al (22) were of the Beijing lineage, and interestingly, three of the four Beijing lineage isolates were isolated from patients who were born in China.…”
Section: Discussionmentioning
confidence: 80%
“…High rates of Mtb transmission in high endemicity populations increase the prevalence of mixed infections, and therefore in majority of cases, the standard rule remains to treat patients with mixed populations for both DS-TB and DR-TB. Furthermore polydrug-resistant strains should be analyzed for RIF resistance as studies have demonstrated that the failure and relapse rates are almost similar in isolates with a recognized or disputed rpoB mutation [53] . Patients with disputed rpoB mutations should be treated for MDR-TB ± high dose rifampicin as the clinical outcome is worse with standard treatment [54] , [55] .…”
Section: Discussionmentioning
confidence: 99%
“…GeneXpert and LPA are the two WHO approved molecular diagnostic tests that detect mutations in the RRDR of the rpoB gene for the earlier diagnosis of rifampicin resistance in clinical specimens and culture isolates. However, these tests are not specific and they do not detect mutations outside of the 81bp RRDR of the rpoB gene of Mtb, which contains 95% of known rifampicin resistance-associated codons, leading to false-negative rifampicin resistance [13,39,40]. In addition, MGIT 960 culture, which is the current standard resistance test endorsed by the WHO to validate novel molecular assays may miss occult rifampicin resistance due to 'disputed' mutations [39].…”
Section: Discussionmentioning
confidence: 99%
“…However, these tests are not specific and they do not detect mutations outside of the 81bp RRDR of the rpoB gene of Mtb, which contains 95% of known rifampicin resistance-associated codons, leading to false-negative rifampicin resistance [13,39,40]. In addition, MGIT 960 culture, which is the current standard resistance test endorsed by the WHO to validate novel molecular assays may miss occult rifampicin resistance due to 'disputed' mutations [39]. This is due to the pre-set standard conditions of rifampicin critical concentration of 1 μg/ml.…”
Section: Discussionmentioning
confidence: 99%